PbTiO3/PbFe12O19 nanocomposites: Green synthesis through an eco-friendly approach. (February 2016) - Ansari, Fatemeh; Sobhani, Azam; Salavati-Niasari, Masoud
Abstract: The present work focused on the synthesis and characterization of PbTiO3 /PbFe12 O19 nanocomposites through a new sol–gel auto-combustion route. First, a sol of PbFe12 O19 was obtained, from metal nitrates and maltose as reductant. Second, a sol of titanat by mixing of tetra-n-butyl orthotitanate, diethanoamin and ethanol was prepared. Then obtained sol was added to the PbFe12 O19 sol. The effects of Pb:Fe, Pb:maltose, Ti:Pb ratios and calcination temperature and time on the morphology, particle size, purity and phase of nanocomposites were investigated. The nanocomposites were characterized using XRD, SEM, TEM, EDS and IR. Vibrating sample magnetometer was used to study the magnetic property of the nanocomposites.